Formation of deformation substructures in FCC crystals under the influence of point defect fluxes; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Matveev M. V. (Materials Science in Mechanical Engineering, 2016)
Title screen